Effects of a High-Grain Diet With a Buffering Agent on Milk Protein Synthesis in Lactating Goats - He, Meilin; Nie, Xintian; Wang, Huanhuan; Yan, Shuping; Zhang, Yuanshu (Frontiers in Veterinary Science, 2021)
Chinese dairy industries have developed rapidly, providing consumers with high quality sources of nutrition. However, many problems have also appeared during the development process, especially the low quality of milk. To improve milk quality, a large amount of concentrated feed is usually added to the feed within a certain period of time, which increases the milk production to a certain extent. However, long-term feeding with high-concentration feed can lead to subacute rumen acidosis. Therefore, the present study aimed to determine the effect of adding a buffer on subacute rumen acidosis, and the improvement of milk production and milk quality. We also aimed to study the mechanism of promoting breast lactation. To understand the effects of high grain diets and buffers on amino acids in jugular blood and the effects of amino acids on milk protein synthesis, Milk-Testing™ Milkoscan 4000, commercial kits, and high-performance liquid chromatography (HPLC) measurements were integrated with the ilk protein rate, the amino acid concentration in jugular venous blood samples, quantitative real-time PCR, comparative proteomics, and western blotting to study differentially expressed proteins and amino acids in mammary gland tissues of goats fed high-grain diets. Feeding lactating goats with high-grain diets and buffers increased the percentage of milk protein in milk, significantly increased the amino acid content of jugular blood (p < 0.05), and increase the amino acid transporter levels in the mammary gland. Compared with the high-grain group, 2-dimensional electrophoresis technology, matrix-assisted laser desorption/ionization-time of flight/time of flight proteomics analyzer, and western blot analysis further verified that the expression levels of beta casein (CSN2) and lactoferrin (LF) proteins in the mammary glands of lactating goats were higher when fed a high-grain diets and buffers. The mechanism of increased milk protein synthesis was demonstrated to be related to the activation of mammalian target of rapamycin (mTOR) pathway signals.